Reversible posterior leucoencephalopathy syndrome associated with bone marrow transplantation Leucoencefalopatia posterior reversível associada a transplante de medula óssea - Hélio A.G. Teive; Ivar V. Brandi; Carlos H.F. Camargo; Marco A. Bittencourt; Carmem M. Bonfim; Maria L. Friedrich; Carlos R. de Medeiros; Lineu C. Werneck; Ricardo Pasquini (Arquivos de Neuro-Psiquiatria)
Reversible posterior leucoencephalopathy syndrome (RPLS) has previously been described in patients who have renal insufficiency, eclampsia, hypertensive encephalopathy and patients receiving immunosuppressive therapy. The mechanism by which immunosuppressive agents can cause this syndrome is not clear, but it is probably related with cytotoxic effects of these agents on the vascular endothelium. We report eight patients who received cyclosporine A (CSA) after allogeneic bone marrow transplantation or as treatment for severe aplastic anemia (SSA) who developed posterior leucoencephalopathy. The most common signs and symptoms were seizures and headache. Neurological dysfunction occurred preceded by or concomitant with high blood pressure and some degree of acute renal failure in six patients. Computerized tomography studies showed low-density white matter lesions involving the posterior areas of cerebral hemispheres. Symptoms and neuroimaging abnormalities were reversible and improvement occurred in all patients when given lower doses of CSA or when the drug was withdrawn. RPLS may be considered an expression of CSA neurotoxicity. A síndrome de leucoencefalopatia posterior reversível (SLPR) tem sido descrita em pacientes com insuficiência renal, eclâmpsia, encefalopatia hipertensiva e em pacientes que recebem terapia imunossupressora. O mecanismo pelo qual os agentes imunossupressores podem causar a síndrome ainda não são conhecidos, porém estão provavelmente relacionados aos efeitos citotóxicos destes agentes no endotélio vascular. Relatamos oito pacientes que receberam ciclosporina A (CSA) após transplante de medula óssea alogênico ou para tratamento de anemia aplástica severa e que desenvolveram a SLPR. Os sinais e sintomas mais comuns foram convulsões e cefaléia. A disfunção neurológica ocorreu simultaneamente ou precedida por elevação da pressão arterial sistêmica e disfunção renal aguda em seis pacientes. O exame de tomografia computadorizada do crânio demonstrou a presença de áreas de baixos valores de atenuação na distribuição da substância branca, envolvendo áreas posteriores de ambos os hemisférios cerebrais. O quadro clínico e as anormalidades tomográficas foram reversíveis; a melhora ocorreu em todos os pacientes em que as doses de CSA foram reduzidas ou quando a droga foi retirada. A SLPR pode ser considerada uma expressão de neurotoxicidade da CSA.